KEBERHASILAN WIRAUSAHA KOPI KOKO DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Mulyana, Agnita Lara; Natuna, Daeng Ayub; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Abstract: This research is motivated by the success of entrepreneurship, so that the researcher wants to examine the success of the koko coffee entrepreneurship in Gunung Toar District, Kuantan Singingi Regency. So that the researcher formulates the problem under study, which are the factors that influence the success of koko Coffee entrepreneurship in Gunung Toar District, Kuantan Singingi Regency?. This type of research is descriptive with a quantitative approach. The population in this study were 62 koko coffee coffee entrepreneurs in Gunung Toar District, Kuantan Singingi Regency. The technique used is Simple Random Sampling. After the ijicoba was done, the number of valid data was 37 and the invalid data were 5. All invalid items were discarded meaning they were not used in the study, because all valid items represented indicators and sub indicators. It is known that the mean and standard deviation (SD) found in 2 indicators with a total sample of 38 koko coffee coffee entrepreneurs in filling out the questionnaire instrument of this study. It can be seen that the first indicator is the internal factor with an average mean of 3,97 and SD of 0,75 which is a fairly high interpretation. Then the indicators of the two external factors with a mean value of 3,93 and SD of 0,78 are quite high in interpretation. As well as for the total average number of indicators, the mean value is 3,95 and SD 0,76 which is in the quite high interpretation. So, the highest of these 2 indicators is the internal factor with a mean of 3,97 and SD of 0,75. This means that koko coffee entrepreneurs become entrepreneurs due to internal factors that influence it.Key Words: The Success Of Entrepreneurship